Preparing Counsellors for HIV Positive Youth: A model for curriculum development - Roberts, Jillian; Marshall, Anne (Canadian Journal of Counselling and Psychotherapy, 2007)
All counsellors will need to be equipped to meet the needs of individuals with HIV. However, this is especially true for counsellors working in the school environment. The arrival of children with HIV in school systems poses a challenge for school counsellors-a challenge for which they need to be well prepared. It is therefore extremely important that counsellor training programs include a component on HIV awareness in their curriculum. The purpose of the present paper is to outline the cornerstones of best practice that may serve to guide the development of such curriculum.